Avaliação da presença de sintomas psiquiátricos e disfunções cognitivas em um grupo de pacientes com Distonia Cervical Idiopática em um centro terciário - Denise Maria Meneses Cury Portela (2020)
Introduction: Dystonia is currently defined as a movement disorder characterized by sustained or intermittent muscle contractions, which cause abnormal and often repetitive movements and postures. Recent studies demonstrate that, despite the definition exclusively related to motor aspects, there are non-motor manifestations in patients diagnosed with dystonia. There has been great emphasis on aspects related to psychiatric disorders, cognitive impairment, pain, sleep and abnormalities in sensory perception. Some publications demonstrate that non-motor symptoms are important predictors with respect to quality of life. Objectives: Investigation of the presence of psychiatric symptoms and cognitive impairment in patients with idiopathic cervical dystonia in a tertiary center. Methods: Cross-sectional, descriptive and analytical study which included 31 patients diagnosed with idiopathic cervical dystonia and 31 healthy control subjects matched by sex, age and education. The sample was evaluated by means of a clinical protocol which included standardized scales and interviews to obtain data on psychiatric symptoms and cognitive disorders. The instruments used were Mental State Mini Exam, Brief Cognitive Test Battery, Digit symbol substitution test, Hayling Test, Emotion Identification Test, Frontal Evaluation Test Battery, Mini International Neuropsychiatric Interview, Yale Brown Obsessive Compulsive Scale. The severity of dystonia was assessed by the Toronto Western Spasmodic Torticollis Rating Scale. Results: Regarding the psychiatric symptoms evaluated in this study, statistically significant differences were identified in the prevalence of current depressive episode (38.7% and p = 0.020) and depressive episode with melancholic symptoms (32.3% and p = 0.003) among patients diagnosed with idiopathic cervical dystonia compared to the prevalence of 12.7% and 3.2% respectively among participants in the control group. Regarding cognitive aspects, no statistically significant difference was found in this study for results of the tests applied to assess the cognitive domains: verbal and visual episodic memory, attention, executive function and visuo-constructive skills. Our study observed statistically significant difference between patients with cervical and idiopathic dystonia and healthy control subjects to identify the following emotions: anger and neutral (p < 0.05) on the emotion recognition test. Conclusions: Except for a higher prevalence of depression, the only parameter capable of distinguishing patients with cervical dystonia in this study was the facial emotion recognition test. Our study showed no difference when comparing patients with cervical dystonia and control subjects in the test of visual and verbal episodic memory, attention, visuo-constructive skills and executive function.